Penerapan Metode Adaptive Neuro Fuzzy Inference System (Anfis) Untuk Memprediksi Kepuasan Pasien Rawat Jalan Terhadap Sistem Pelayanan Kesehatan (Studi Kasus Puskesmas Desa Tarutung Kerinci) - HAIRUL CANDRA (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT The main objective of this study was to analyze the problem of outpatient satisfaction in Rural Health Center Desa Gedang Sungai Penuh. Respondents who are the subject of this study amounted to 50 people. Research using surveys, sampling methods and questionnaires as a tool to collect data. This study uses Adaptive Neuro-Fuzzy Inference System (ANFIS). Data were analyzed using MATLAB software. This study shows the results of the service as follows: (1) Very Good (2) Satisfactory (3) Very Unsatisfactory. By understanding the variables that affect the level of patient satisfaction, management will know how important the variable. So, hopefully they can decide to maintain and develop it in order to obtain patient satisfaction. Reserve Word : Reliability, Responsiveness, Assurance, Emphaty, Tangible, dan ANFIS.